GROWTH SPURT AND BMI OF SCHOOL OF 9 TO 14 YEARS OF URBAN AREA OF THE CITY OF ARAPIRACA-AL (Fiep Bulletin - online, 2013)
The monitoring of height and BMI are important indicators of quality of life, and enable you to check the health status over certain periods of a given population. The present study aimed to evaluate the stature and BMI of schoolchildren of both sexes between the ages of 9 and 14 years. The sample consisted of 1522 students of both sexes, with ages 9-14 years, with 745 males and 777 females, chosen at random among students duly enrolled in four schools in the urban municipal schools of Arapiraca - AL, in 2010. The data collection was used: a stadiometer and balance Sanny ® Techline ® BAL-150PA. The results were obtained from tables regulations proposed by the WHO (2007) and the cut points suggested by Cole et al. (2000). For the treatment of the data was used statistics of central tendency and dispersion values ??(mean and standard deviation). The results demonstrate that both the stature, the BMI of the male students and female are within normal limits. We conclude that both the stature, as the students' BMI males and females in this study were within normal limits.
Keywords: Height; BMI; School.